2014
DOI: 10.1128/jcm.00505-14
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of New CMRSA7/USA400 Methicillin-Resistant Staphylococcus aureus spa Types in Alberta, Canada, from 2005 to 2012

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has become one of the most significant pathogens affecting global public health and health care systems. In Canada and the United States, the spread of MRSA is primarily attributed to a single dominant epidemic clone: CMRSA10/USA300. Despite this, the CMRSA7/USA400 epidemic clone has been reported to be the predominate epidemic clone in several Canadian provinces and some parts of the United States. This study examined the epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Although the general trend found reports of increasing prevalence over time, a small number of studies reported lower MRSA prevalence rates. Li et al [ 21 ] reported a MRSA prevalence of 0.32 per 100,000 Albertans in 2005, and Bracco et al [ 22 ] reported a MRSA prevalence of only 1.1% among ICU patients in Montreal from 2002 to 2004 inclusive, suggesting that there may be some site-to-site variation in the detection or prevalence of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…Although the general trend found reports of increasing prevalence over time, a small number of studies reported lower MRSA prevalence rates. Li et al [ 21 ] reported a MRSA prevalence of 0.32 per 100,000 Albertans in 2005, and Bracco et al [ 22 ] reported a MRSA prevalence of only 1.1% among ICU patients in Montreal from 2002 to 2004 inclusive, suggesting that there may be some site-to-site variation in the detection or prevalence of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…The USA300 strain belongs to ST8 and has a high prevalence and morbidity rate over a period of time 21 . The MW2 (USA400) epidemic clone has also been the predominant epidemic clone in several Canadian provinces and some parts of the United States 22 . SA759 belongs to ST239, which is a major cause of MRSA infections in Asian hospitals 23 .…”
Section: Introductionmentioning
confidence: 99%
“…These strains colonize mucosal surfaces and cause life-threatening infections, most notably menstrual TSS, which occurs in otherwise healthy women ( 13 ). USA400 strains are also community associated, are frequently isolated in the upper Midwest and southwestern Alaska, and have emerged as the predominant MRSA type in western Canada ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%